Determination of heavy metals concentration in dry anchovies / Zaidatul Norakmar Mohd Ridah - Mohd Ridah, Zaidatul Norakmar (Faculty of Applied Sciences, 2017)
This study aimed to determine the concentration of essential heavy metals (zinc, copper) and non-essential heavy metals (cadmium, lead) in four different types of dried anchovies that were obtained from retail shops. All samples were classified as Type A (big, peel), Type B (big, unpeel), Type C (small, unpeel), and Type D (small, peel). Heavy metals were analysed using Flame Atomic Absorption Spectrophotometer (FAAS). Concentration of zinc was the highest in all samples which is 0.93 mg/kg. Lead shows the lowest concentration which is below the detection limit of FAAS. Meanwhile, concentration of copper and cadmium were 0.047 mg/kg and 0.043 mg/kg, respectively. All of heavy metals in samples were below the permissible limits that had been listed by Malaysian Food Regulation (1985). Hazard index (HI) for Type A, Type B, Type C and Type D were 2.31 x 10-5, 2.57 x 10.-5, 2.22 x 10-5 and 2.48 x 10-5, respectively. All samples are safe to consume and there is no potential non-carcinogenic risk since the HI values were below unity.